Music audio emotion regression using the fusion of convolutional neural networks and bidirectional long short-term memory models - Yi Qiu; Yu Lin; Yun Lin (PeerJ Computer Science)
Music emotion regression (MER) is a vital field that bridges psychology and music information retrieval. Music has the powerful ability to evoke a wide range of human emotions, from joy and sadness to anger and calmness. Understanding how music influences emotional states is essential for grasping its psychological effects on individuals. This research presents an innovative model that combines convolutional neural networks (CNNs) with bidirectional long short-term memory (BiLSTM) networks to analyze and predict the emotional impact of musical audio. The model uses CNNs to detect temporal patterns and BiLSTMs to interpret sequences in both forward and backward directions, enhancing its ability to capture the complex structure of musical data. Additionally, a multi-head attention mechanism is incorporated to improve the model’s expressiveness and generalizability, making it especially effective for handling intricate sequential tasks and large datasets. The model’s performance was evaluated through sentiment prediction using extensive, publicly available datasets comprising over 9,000 musical excerpts. Results show that the proposed model significantly outperforms existing methods in MER, achieving an R-squared value of 0.845, indicating an excellent fit with the empirical data.